Energy efficient flow path for improving electrolyte distribution in a vanadium redox flow battery. (15th February 2022) - Sharma, Harsh; Kumar, Milan
Summary: Aiming to improve electrolyte distribution in flow batteries at lower pumping cost, a sinusoidal wave‐type serpentine (SWS) flow pattern was designed and fabricated on graphite plate. The performance of the channel with graphite felt electrode, employing in vanadium redox flow battery, was analyzed by polarization curves and electrochemical impedance spectroscopy (EIS) measurements, obtained by varying flow rates of electrolyte. The pressure drop of the half‐cell assembly was measured by varying water flow rates. Results show that increasing flow rate reduces potential loss. Mass transfer overpotential is low even at 30 mL/min, and at 120 mL/min, the overpotential is negligible even at very high current density of 500 mA/cm 2 . The iR ‐free power density monotonically increases with current density. The EIS measurements show that charge transfer resistance decreases with increasing flow rates and is lower than that for conventional serpentine flow pattern. The pressure drop across the cell is also lower. These results clearly indicate that better electrolyte distribution is achieved using SWS channels at lower pumping cost. Abstract : A sinusoidal wave‐type serpentine (SWS) flow pattern was fabricated, aiming higher better distribution of electrolyte at low pumping cost. At high flow rate, mass transfer resistance is negligible even at higher current densities. The cell experiences lower pressure drop than using conventional serpentine channel.